Least-squares symmetric solution to the matrix equation AXB = C with the norm inequality constraint. Issue 9 (1st September 2016) - Xie, Dongxiu; Xu, An-Bao; Peng, Zhenyun
Abstract : In this paper, an iterative method to compute symmetric least-squares solution of the matrix equation AXB = C with the norm inequality constraint is proposed. For this method, without the error of calculation, a desired solution can be obtained with finitely iterate steps. Numerical experiments are performed to illustrate the efficiency and application of the algorithm.